Database management systems : - Post, Gerald V. (McGraw-Hill / Irwin, 2005)
In today's increasingly decentralized and insecure business arena, effective database management has taken on a whole new urgency. "Database Management Systems, Third Edition," introduces and explains core concepts of database design, development, and administration. Special sections demonstrate how to first evaluate security threats and then design vital security components and integrate them into each application. Applied exercises and cases bring facts and data into the real world.